Neurodegeneration: Microglia: Nf-Kappab Signaling Pathways - Singh, Aditya; Ansari, Vaseem Ahamad; Mahmood, Tarique; Ahsan, Farogh; Wasim, Rufaida (Drug Research, 2022)
Microglia is cells of mesodermal/mesenchymal origin that migrate into the central nervous system (CNS) to form resident macrophages inside the special brain microenvironment. Intact with both neuronal and non-neuronal cells, microglia is highly active cells. Continuous process extension and retraction allows microglia to scan the brain parenchyma for threats. They are also able to change their morphology from ramified to amoeboid, which is a sign of cell activity. In response to pleiotropic stimuli such as neurotransmitters, cytokines, and plasma proteins, microglia express a diverse range of receptors. As controllers of synaptic activities and phagocytosis of developing neurons, they serve a critical role in the healthy brain and have significant effects on synaptic plasticity and adult neurogenesis. A frequent cause of hypoparathyroidism is a mutation in the gene glial cells missing-2 (GCM2). Neonatal hypoparathyroidism has an amorphic recessive GCM2 mutation, while autosomal dominant hypoparathyroidism has a dominant-negative GCM2 mutation. Curiously, familial isolated hyperparathyroidism has been associated with activating GCM2 mutation. In addition to seizures, neurocognitive impairment, carpopedal spasm, tingling and numbness are common clinical manifestations of hypoparathyroidism. Biogenic amines are a group of four neurotransmitters that belong to that category and these include serotonin, dopamine, norepinephrine, and epinephrine. Numerous antidepressants prevent the reuptake from occurring the brain-gut axis is hardwired through the CNS, enteric nervous system (ENS), neuroendocrine linkages and highly innervated nerve plexuses.
Keywords: Microglia; Central Nervous System; Enteric Nervous System; Neurocognitive impairment; Receptor; Dopamine.